2017
DOI: 10.3178/hrl.11.79
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different land-use on suspended sediment dynamics in Sabah (Malaysian Borneo) – a view at the event and annual timescales

Abstract: Abstract:Suspended sediment concentrations (SSC) and the duration of high SSC are important for river ecology and water resource conservation. Using annual and storm-event datasets, this paper explores the hypothesis that key suspended sediment variables increase along a land-use disturbance gradient in hilly terrain in Sabah (Malaysian Borneo). Five small (1.7-4.6 km 2 ) catchments of increasing disturbance history -primary forest, old growth virgin jungle reserve, twice-logged forest, multiple-logged forest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In fact, these forests contribute to maintaining the quality of surface water in particular. As such, in their study, Nainar et al (2017) underlined some contributions of rainforest to the preservation of water quality and reduced erosion. However, the results of many articles analyzed in this study indicated that forest areas are gradually decreasing in Malaysia, mainly due to the conversion actions to either agricultural or urban development activities.…”
Section: Impact Of Forest Land Use On Water Qualitymentioning
confidence: 93%
“…In fact, these forests contribute to maintaining the quality of surface water in particular. As such, in their study, Nainar et al (2017) underlined some contributions of rainforest to the preservation of water quality and reduced erosion. However, the results of many articles analyzed in this study indicated that forest areas are gradually decreasing in Malaysia, mainly due to the conversion actions to either agricultural or urban development activities.…”
Section: Impact Of Forest Land Use On Water Qualitymentioning
confidence: 93%
“…Sediment yield increases in the early stages of oil palm establishment when compared to forest cover and agroforest (Carlson et al 2014, Nainar et al 2017. An increase has been also observed in soil erosion in oil palm compared to forest (Gharibreza et al 2013, Nainar et al 2017 (figure 5). Erosion and sediment concentration in streams increase due to oil palm establishment, after forest conversion.…”
Section: Fluvial Processesmentioning
confidence: 93%
“…For example, compared to rainforest, sediment yield increased with differences between 19 000 ± 3400 mg h −1 ha −1 in juvenile plantations and 8000 ± 2000 mg h −1 ha −1 in mature plantations (Carlson et al 2014). In another study, annual suspended sediment concentration discharge in an oil palm catchment was estimated to be 4-12 times greater than primary and multiple-logged forest catchments (Nainar et al 2017). Similarly, in a 5 years old oil palm plantation, erosion was higher (46 kg ha −1 ) than in forests (13 kg ha −1 ) (Jaya et al 2018).…”
Section: Fluvial Processesmentioning
confidence: 95%
“…This sudden in ux of material may cause ooding and alter the river's morphology by accelerating erosion and altering the geometry of the channel. Complicating matters, these are all additional factors to the naturally occurring drivers of mass movement, namely climate, weathering, stream ow, and other characteristics such as soil type, vegetation, and land-cover that in uence geomorphological changes in an area (Nainar et al 2017; Sidle et al 2006). Nevertheless, Xue et al (2013) discovered that signi cant mass movements were governed by episodic seismic events rather than these recurrent factors.…”
Section: Introductionmentioning
confidence: 99%